Influence of equine (eCG) and human (hCG) chorionic gonadotropins on corpus luteum development and pregnancy rate in bovine embryo recipientes - Mattos, Ana Clara Degan (2024)
We aimed in this study to compare the effects of different hCG doses on corpus luteum (CL) development and effects of splitting the eCG dose in two moments during the ovulation synchronization protocol on pregnancy per embryo transfer (P/ET) in beef cows. In Experiment 1, non-lactating Nelore cows at two days after spontaneous ovulation were assigned into four groups: C (no treatment; n=13), hCG-500 (i.m.; 500IU hCG; Chorulon, MSD; n=12), hCG-1000 (1000IU hCG; n=13) and hCG-2000 (2000IU hCG; n=12). Luteal area (LA) and blood perfusion (BP) were determined by B-mode and color-Doppler ultrasonography, respectively, and P4 assayed every 48 hours for 14 days. In Experiment 2, primiparous crossbred suckled cows (Nelore x Angus) were submitted to a P4/E2-based protocol on Day 0 (D0). Cows were divided into four groups (2x2 factorial): control (300IU eCG on D9 [Folligon, MSD]; n=227), eCG/2x (150IU eCG on D7 and D9; n=222), hCG (300IU eCG on D9 and 1000IU hCG on D14; n=221) and eCG/2x+hCG (eCG on D7 and D9 and hCG; n=219). On D9, P4 device was removed, 0.53mg cloprostenol sodium and 1mg estradiol cypionate were injected and the dominant follicle (DF) size was evaluated in 501 females. On D18, cows with a CL received a fresh expanded blastocyst, the LA and BP were evaluated in all females and plasma P4 concentrations were determined (n=271). Data were analyzed by ANOVA, Fisher′s exact test or logistic regression of SAS. In Exp1, rate of accessory CL (aCL) differed (P<0.05) among the groups (C, 0%C; hCG- 500, 8%BC; hCG-1000, 61.5%A; hCG-2000, 41.6%AB). The total LA (sum of primary CL + aCLs) was greater (P<0.05) in the hCG-1000 and hCG-2000 groups than in the C, whereas the hCG- 500 did not differ from the others. For BP, there was no difference (P>0.1). For P4 concentration, an interaction between treatment and time (P=0.04) occurred, which the concentration was greater on days 6 to 12 in hCG-1000 and 2000 groups. In Exp2, DF size (mm) on D9 tended (P=0.07) to be larger in the groups receiving eCG/2x (11.1±0.2 vs. 10.6±0.2). The rate of cows with>1CL on D18 was greater (P>0.01) in hCG-treated cows (5.2% vs. 0.5%). P4 concentrations on D18 were greater (P>0.01) in hCG-treated cows, regardless of the eCG treatment (5.0 vs. 3.9 ng/mL). For LA, a greater increase (P>0.01) in LA occurred by the association of hCG and eCG/2x treatments compared to its significant isolated effects. For BP, an interaction of eCG and hCG treatments was observed (P=0.01), as indicated by the absence of effect of hCG in cows receiving a single eCG dose and the reduction of BP by the hCG treatment in eCG/2x-treated cows. P/ET at 28 days post ET was greater (P=0.01) in eCG/2x (53%) and hCG (52%) groups than in control (41%) but did not differ in eCG/2x+hCG (46%) group compared to others. The same pattern remained for P/ET at 60-150 days post ET, which eCG/2x (47%) and hCG (46%) groups were greater than control (37%) and eCG/2x+hCG did not differ (37%) compared to others. In conclusion, the administration of at least 1000IU hCG increases the LA and P4 concentrations and P/ET but does not enhance luteal BP and P/ET. The eCG administration in two moments during DF growth improves DF and P/ET in primiparous recipient beef cows, but its association with hCG is not indicated as it potentially reduces luteal BP and did not increase P/ET.